Проблемы определения вероятности поражения человека избыточным давлением взрыва - Ivanitskiy, Александр; Mikanovich, Андрей; Petriko, Елена (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The article presents an overview of the situation with the explosions in industrial and civil objects. Critical analysis of regulatory methodology for determining the conditional probability of people injury by overpressure of the explosion. The directions for further research defined.